Concentração industrial no Brasil : um estudo incorporando o efeito de vizinhança - Vignandi, Rafaella Stradiotto (2013)
The goal of this dissertation is to account for the effects of neighborhood indices of spatial concentration, in order to examine possible changes in the status of some sectors of the manufacturing industry in the regions in Brazil in the years 1995-2010. To do so, it examines the current state of development of the industrial sector and its key policies in the national context after the Real Plan. And in a second step, we calculate the concentration indices spatially unweighted, Herfindahl, Concentration Geographic-Press, Ellison-Glaeser, later to contrast them with the same indicators spatially modified by adding the analysis of the Moran's I. In order to consider the results obtained through this study of the Brazilian manufacturing industry, we can reveal that the concentration indices spatially weighted and show the possible deconcentration of most sectors that comprise manufacturing industry in the period 1995-2010. Specifically, through indices calculated spatially can see clearly a devolution process in some economically important sectors. The only sector that showed an increase in the level of concentration was related to the Division 23 Manufacture of coke, Petroleum Refining, Nuclear Fuel Development and Production of Alcohol. Thus, we can conclude that the concentration indices spatially weighted compared with non-weighted elucidate and leave more on the real evidence of the effects of interference neighborhood, to consider the presence (or not) the neighbors in the analysis and more specifically the deconcentration of industrial activities in Brazil.